Mucocele showing both retention and extravasation phenomenon: An eccentric case report - Preethi Arunachalam; Dineshkumar Thayalan; Abdul Razak; K Abiramivarman; Abishek Gowtham; Abinaya Rajesh (Wolters Kluwer Medknow Publications, 2021)
An unusual report of mucocele presenting with both retention type and extravasation phenomenon has been presented. A 44-year-old male patient presented with a swelling in the commissure of the lip region for the past 2 months. A thorough clinical examination and history taking gave a diagnosis of a mucocele. This case highlights and discusses the histopathological features, differential diagnosis, and the theories behind the presentation of this rare case report.